Harta dalam Pemanfaatan Filantropi Islam - Ahmad Fihri (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
Treasure is a fundamental component in human life, aspects of dharuriyyah that can not be left behind and put aside. With such property man can meet the needs and desires, both material and immaterial. In order to fulfill those needs then there is a process of relationship of interests and needs among human beings who are human beings can not live alone, but need each other. In this context, property as an object in various transactions, such as buying and selling, ijara, rahn, musharaka, and other muamalah akad, until the status of property belongs to someone. etymologically al-maal is defined as anything that can bring peace, comfort in the form of material/physical and in the form of benefits, serrta can be fully owned by the way kasab (effort). Islam as a religion that syumul his teachings have set human life in get it, use it to be useful for self, family, and community.